Outdoor Office Work – An Interactive Research Project Showing the Way Out - Petersson Troije, Charlotte; Lisberg Jensen, Ebba; Stenfors, Cecilia; Bodin Danielsson, Christina; Hoff, Eva; Mårtensson, Fredrika; Toivanen, Susanna (Frontiers in Psychology, 2021)
The physical boundaries of office work have become increasingly flexible. Work is conducted at multiple locations outside the office, such as at clients’ premises, at home, in cafés, or when travelling. However, the boundary between indoor and outdoor environment seems to be strong and normative regarding how office work is performed. The aim of this study was to explore how office work may be conducted outdoors, understanding how it is being experienced by office employees and identifying its contextual preconditions. Based on a two-year interactive research project, the study was conducted together with a Swedish municipality. Fifty-eight participants engaged in the collaborative learning process, including forty half-day workshops and reflective group discussions, co-interviews, and participants’ independent experimentation of bringing work activities outdoors. Data was collected via interviews, group discussions and a custom-made mobile application. The results showed that a wide range of work activities could be done outdoors, both individually and in collaboration with others. Outdoor work activities were associated with many positive experiences by contributing to a sense of wellbeing, recovery, autonomy, enhanced cognition, better communication and social relations, but were also associated with feelings of guilt and illegitimacy. Conditions of importance for outdoor office work to happen and function well were found in the physical environment, where proximity to urban greenspaces stood out as important, but also in the sociocultural and organizational domains. Of crucial importance was managers’ attitudes, as well as the overall organizational culture on this idea of bringing office work outdoors. To conclude, if working life is to benefit from outdoor office work, leaders, urban planners and policymakers need to collaborate and show the way out.